ANALISIS KINERJA PEGAWAI NEGERI SIPIL DI KANTOR KECAMATAN TEMBALANG KOTA SEMARANG - Manurung, Herawaty; Nurcahyanto, Herbasuki; Hariani, Dyah (Journal of Public Policy and Management Review, 2013)
Employee performance is the result or output obtained from each employee who works at the institution. In this study . This research relates to employee performance analysis in Sub-district Office Tembalang, Semarang city, is cheks relationship between employee capability, employee discipline, employee motivation with employee performance. Sample is taken by using the method of sampling techniques jenuh/sensus. Sampling jenuh is used when population in a relatively small in amount or less than 30 people, so that all members of the sample population is used as much as people. Technical analysis is a technique used Rank analysis of Kendall and Kendall's Concordance, which is used to determine whether there is a relationship between variables, and the results of analysis to prove:1. Correlation between employee capability variable with employee performance variable showed a correlation coefficient of 0,219 with a significant level of 0,103 > 0,05 which means there is not significant relationship between employee capability with employee performance.2. Correlation between employee discipline variable with employee performance variable showed a correlation coefficient of 0,332 with a significant level of 0,015 < 0,05 which means there is a significant relationship between employee discipline with employee performance3. Correlation between employee motivation variable with employee performance variable showed a correlation coefficient of 0,262 with a significant level of 0,049 < 0,05 which means there is a significant relationship between employee motivation with employee performance.4. Correlation between employee capability variable, employee discipline variable, employee motivation variable with employee performance concurrently having a significant relationship, it is retrieved from the result chi-square of 66,101.